IMPLEMENTASI E-GOVERNMENT BERBASIS SERVICE ORIENTED ARCHITECTURE (SOA) PADA KANTOR KECAMATAN NATAR LAMPUNG SELATAN - Sukatmi Sukatmi; Afriyanto Afriyanto (Jurnal informasi dan komputer, 2019)
E-government is short for from plan to implement the electronic the government .E-government is one of form or model of a system of government based on the power of digital technology, in which all in administrative work, the service for people, supervision and control section of the source of its power belonging to an organization concerned, financial, of taxes had not yet, levies which may be collected, white collar workers and rontje participated in this festival was brought under control in one system. E-government an outgrowth new as in order an increase of services the public allowing them to the main effort to lower the utilization of technology information and communication so that public services to village heads to be more transparent, accountable, effective and efficient. Offices of head of subdistricts natar is one of government institutions that is in south sample is taken at Lampung the Lampung provincial .As an institution of governance which had been has a duty and the obligation of serving the needs of the people is required to be able to always improve the quality of these services . One of the efforts to do is build e-government. through community service hence the need to do research in order to produce a e-government based Service Oriented Architecture (SOA) to the district office Natar Lampung South. Method of development systems used is Extreme Programming with the design of the Unified Modeling Gig Language (UML) and using the alchemy of PHP programming language, CSS and java. programing The end result of this research is e-government program having many access facilities for the office Natar Lampung South, so the society should not do went directly to the office in the search information and some services that needed.